'Power, regulation and physically active identities': the experiences of rural and regional living adolescent girls. Issue 1 (2nd January 2016) - Casey, M.; Mooney, A.; Smyth, J.; Payne, W.
Abstract : Drawing on interpretations of Foucault's techniques of power, we explored the discourses and power relations operative between groups of girls that appeared to influence their participation in Physical Education (PE) and outside of school in sport and physical activity (PA) in rural and regional communities. Interviews and focus groups were conducted in eight secondary schools with female students from Year 9 ( n = 22) and 10 ( n = 116). Dominant gendered and performance discourses were active in shaping girls' construction of what it means to be active or 'sporty', and these identity positions were normalised and valued. The perceived and real threat of their peer's gaze as a form of surveillance acted to further perpetuate the power of performance discourses; whereby girls measured and (self) regulated their participation. Community settings were normalised as being exclusively for skilled performers and girls self-regulated their non-participation according to judgements made about their own physical abilities. These findings raise questions about the ways in which power relations, as forged in broader sociocultural and institutional discourse–power relations, can infiltrate the level of the PE classroom to regulate and normalise practices in relation to their, and others, PA participation.